BERPIKIR TEORITIS DALAM ILMU PENGETAHUAN: FONDASI TEORI ILMIAH DAN IMPLIKASINYA - Mareta, Angye; Fitrisia, Azmi; Fatimah, Siti (DAS Institute, 2024)
Theoretical thinking is at the core of the development of science, serving as a conceptual framework for understanding, explaining, and predicting phenomena. This study uses the literature review study method. So this study aims to examine the role of theoretical thinking in the formation and development of scientific theories and their implications for scientific progress. Using the literature review study method, this study analyzes a variety of academic sources, including journal articles, books, and research reports, to understand the basic principles of scientific theory formation, the logical structure of theories, and their relevance in various disciplines. The results of the study show that theoretical thinking is not only the basis for the development of science, but also plays an important role in driving innovation, identifying research gaps, and integrating various methodological approaches. In addition, the study found that a solid scientific theory is built on a process of critical reflection and iterative analysis, thus ensuring its reliability in contributing to science universally. The implications of these findings include strengthening the relationship between theory and practice, developing a learning model that focuses on theoretical thinking skills, and increasing cross-disciplinary collaboration in building a more holistic theory. This research is expected to be a reference for academics and practitioners to explore the importance of theoretical thinking in building a strong scientific foundation and applying it effectively in various contexts